Lack of T cell oligoclonality in enzyme-digested synovial tissue and in synovial fluid in most patients with rheumatoid arthritis. - Van Laar, J M (1991)
The dominant presence of specific T-cell populations in the rheumatoid joint as detected by Southern blot analysis of T cell receptor (TCR) gene rearrangements would indicate local antigen recognition and T cell proliferation. We therefore studied TCR beta chain gene rearrangements using a C beta 2 probe in paired samples of T cell populations from synovial tissue and peripheral blood (n = 6) as well as synovial fluid (n = 16) and peripheral blood (n = 18) of patients with rheumatoid arthritis (RA). Peripheral blood mononuclear cells from healthy donors (n = 7) served as a control. T cells were studied directly after isolation or after non-specific expansion with OKT3 monoclonal antibody (MoAb) and T cell growth factor (TCGF). DNA samples were digested with EcoRI and HindIII to detect rearrangements to C beta 1 and C beta 2, respectively. Extra bands were detected in all EcoRI-digested DNA samples prepared from both freshly isolated and non-specifically expanded T cell populations of patients and healthy donors, possibly representing 'common' (V-) D-J rearrangements. Dominant rearrangements were found in only two out of 16 synovial fluid T cell populations (one freshly isolated and one expanded) and not in peripheral blood or synovial tissue derived T cell populations. No extra bands were detected in HindIII-digested DNA samples. To investigate the effect of in vitro culture techniques on rearrangement patterns we studied DNA samples prepared from synovial tissue T cells obtained both by outgrowth from tissue with TCGF or by enzyme digestion and subsequent expansion either with TCGF or with OKT3 MoAb and TCGF. Whereas the latter T cell population yielded 'common' rearrangements, the former T cell populations yielded different dominant rearrangements. These data indicate that oligoclonality of the T cell populations in synovial tissue and synovial fluid of patients with RA is a rare event. The data also show the influence of in vitro culture techniques on the result of TCR gene rearrangement analysis.